Inhibitory activity of Ficus deltoidea var. trengganuensis Aqueous extract on lipopolysaccharide-induced TNF-α production from microglia - Wang, Huiling; Vidyadaran, Sharmili; Mohd Moklas, Mohamad Aris; Baharuldin, Mohamad Taufik Hidayat (Hindawi Publishing Corporation, 2017)
Objective: To explore the effect of Ficus deltoidea (FD) aqueous extracts on the release of tumor necrosis factor-α (TNF-α), the expression of CD40, and the morphology of microglial cells in lipopolysaccharide- (LPS-) activated BV2 cells. Methods. The cytotoxicity of FD extract was assessed by MTS solution. BV2 cells were divided into 5 experimental groups, intervened, respectively, by FD (4 mg/mL) and LPS + FD (0, 1, 2, and 4 mg/mL). Besides, a blank control group was set up without any intervention. TNF-α release was assessed by enzyme linked immunosorbent assay (ELISA). The expression of CD40 was examined by flow cytometry. Immunocytochemical staining was used to show the morphology of BV2 cells. Results: FD extract of different concentrations (1, 2, and 4 mg/mL) had no significant toxic effects on the BV2 cells. FD suppressed the activation of microglia in morphology and reduced TNF-α production and expression of CD40 induced by LPS. Conclusion. FD extract has a therapeutic potential against neuroinflammatory diseases.